Chronicles from the new normal: Urban planning, mobility and land-use management in the face of the COVID-19 crisis. (December 2021) - Corazza, Maria Vittoria; Moretti, Laura; Forestieri, Giulia; Galiano, Giuseppe
Highlights: During the pandemic cities have become "walled" communities as in the Middle Age. The new normal is revamping car-based behaviors and enhancing micromobility. Pedestrian realms are affected by that, without suitable policies. There is a lack of preparedness to manage this change, for transit and public spaces. R&D can learn from this experience to create more preparedness for transit. Abstract: The world is facing new challenges due to the SARS-CoV-2 (Severe Acute Respiratory Syndrome CoronaVirus 2) virus outbreak identified in Wuhan, China in December 2019. The aim of this paper is to investigate and discuss how cities are being managed in the anti-pandemic "new normal". And this in light of unexpected phenomena such as: the on-going modal shift from public transport to private modes vs the new momentum gained by walking, and social lifestyles dictated by confinement first and now by unregulated behavior, also affecting land use. Add to this unpreparedness of pre-pandemic transport policies and the new emerging opportunities; the fresh directions for research and development, for example in the field of urban mobility management. With the additional goal to contribute to further advance the research, the paper also clearly shows that the crisis can be overcome only by considering different fields of action and by considering our common past.